Influence of emotional determinants on the food choices of the Portuguese - Guiné, Raquel (2019)
Food choices are influenced by many factors, such as emotional. When people eat, driven by emotional factors, they often lose control, which may lead to eating disorders. Therefore, this work aimed at studying the influence that emotional determinants had on people’s food choices. It was undertaken a descriptive cross-sectional study by means of a questionnaire on a non-probabilistic sample of 1314 participants. The data was collected among a sample of the Portuguese population and measured if people´s food choices were influenced by emotional determinants. The results revealed that the participants’ food choices were, in general, slightly influenced by emotional determinants (mean scores between –0.5 and 0.5, on a scale from –2 to +2). There were found significant differences in all of the variables under study. The participants, who already experienced an episode of binge-eating, were the ones that obtained the highest mean score (0.63±0.79), meaning that in this case those participants’ food choices were influenced by emotional determinants. These results support the premise that emotional determinants are influenced by the characteristics of each individual and also the existence of a positive association between emotional eating and the presence of eating disorders, especially, binge-eating.